'Come, now a roundel and a fairy song': Shakespeare's A Midsummer Night's Dream and the early modern invitation to the dance. Issue 1 (November 2018) - Hiscock, Andrew
This article considers the status and function of dance in one of Shakespeare's best-known comedies. Equally importantly, it seeks to embed this playtext within the intense and multifaceted cultural debate surrounding dance and performance in early modern England. Dance is explored in legal, moral, philosophical and spiritual terms in the course of this discussion. In its final stages, this article also considers the appeal for dancing which the comedy has exercised for generations of performers down the centuries.